Harmonizing brain magnetic resonance imaging methods for vascular contributions to neurodegeneration. Issue 1 (25th February 2019) - Smith, Eric E.; Biessels, Geert Jan; De Guio, François; de Leeuw, Frank Erik; Duchesne, Simon; Düring, Marco; Frayne, Richard; Ikram, M. Arfan; Jouvent, Eric; MacIntosh, Bradley J.; Thrippleton, Michael J.; Vernooij, Meike W.; et al.
Abstract: Introduction: Many consequences of cerebrovascular disease are identifiable by magnetic resonance imaging (MRI), but variation in methods limits multicenter studies and pooling of data. The European Union Joint Program on Neurodegenerative Diseases (EU JPND) funded the HARmoNizing Brain Imaging MEthodS for VaScular Contributions to Neurodegeneration (HARNESS) initiative, with a focus on cerebral small vessel disease. Methods: Surveys, teleconferences, and an in‐person workshop were used to identify gaps in knowledge and to develop tools for harmonizing imaging and analysis. Results: A framework for neuroimaging biomarker development was developed based on validating repeatability and reproducibility, biological principles, and feasibility of implementation. The status of current MRI biomarkers was reviewed. A website was created at www.harness‐neuroimaging.org with acquisition protocols, a software database, rating scales and case report forms, and a deidentified MRI repository. Conclusions: The HARNESS initiative provides resources to reduce variability in measurement in MRI studies of cerebral small vessel disease.